TRANSMISSÃO PROGRESSIVA DE MAPAS BASEADA EM GIS SERVICES - Costa, David Cavassana (2006)
The Internet has created an good environment for the sharing of geospatial data. In this environment users can transfer, visualize, manipulate and interact with these data sets. This environment not only provides new opportunities for the utilization of geospatial data, but also introduces new problems that should be addressed in order to provide an efficient and effective use of these datasets. One of such problems is related to the use of these spatial datasets in low transfer rate environments, what often becomes an impediment for the publication of those data in the Internet, given the huge volume of data to be transmitted. This paper presents a progressive transmission algorithm for vector maps on the Web, which uses techniques based on the resolution of the client device with the aim of reducing the amount of transmitted data, sending the data incrementally, thus gradually increasing the level of map details. Scale-dependent transmission techniques are combined with simplification and progressive ones, in order to maximize the overall system performance in a Web GIS environment. Furthermore, an architecture based on Web services is presented, that implements the progressive transmission of maps and allows a greater flexibility in the use of this functionality and in the development of clients in different computing platforms.